Aplicação do enxerto conjuntivo subepitelial para recobrimento de recessões em dentes inferiores - Fontanari, Lucas Amaral [UNESP]; Oliveira, Guilherme José Pimentel Lopes de [UNESP]; Souza, João Antonio Chaves de [UNESP]; Frizzera, Fausto [UNESP]; Tonetto, Mateus Rodrigues [UNESP]; Spin Neto, Rubens [UNESP]; Sampaio, Jose Eduardo Cezar [UNESP] (My University, 2013)
Some regions of the oral cavity present anatomical conditions that seem to hinder the result of gingival recessions coverage. Thus, the aim of this case report was to present two surgeries for gingival recessions coverage in the mandibular teeth performed on the same patient with the follow-up of 24 months. Patient RP, 35 years old, male, Caucasian, nonsmoker, systemically healthy, sought care at the clinic of specialization course in Periodontics from the Araraquara Dental School (Foar-Unesp). His main complaint was the gingival recessions within the lower teeth 33, 34, 35, 43, 44 and 45. Besides the aesthetic nuisance, the patient reported occasional dentin sensitivity. For resolution of the case was referred to the technique of subepithelial connective tissue graft associated with a coronally advanced flap. After 2 years of surgery, it was observed an excellent root guards with significant aesthetic improvement of the case. It can be concluded that the subepithelial connective tissue graft technique was effective in covering of type class I gingival recessions of Miller, even in a region that provides a difficult procedure.

Algumas regiões da cavidade oral apresentam condições anatômicas que parecem interferir negativamente no resultado do recobrimento de recessões gengivais. Dessa forma, o objetivo desse relato de caso foi apresentar duas cirurgias de recobrimento de recessões gengivais em dentes mandibulares executadas no mesmo paciente com o acompanhamento de 24 meses. Paciente RP, 35 anos, gênero masculino, leucoderma, não fumante, sistemicamente saudável, procurou atendimento na clínica do curso de especialização em Periodontia da Faculdade de Odontologia de Araraquara – Foar-Unesp. Sua queixa principal eram recessões inferiores nos dentes 33, 34, 35 e 43, 44 e 45. Além do incômodo estético, o paciente relatava sensibilidade dentinária ocasional. Para resolução do caso foi indicada a técnica de enxerto conjuntivo subepitelial associada ao retalho pediculado reposicionado coronalmente. Após dois anos do procedimento cirúrgico, percebeu-se excelente recobrimento radicular com significante melhora estética do caso. Pôde-se concluir que a técnica de enxerto conjuntivo subepitelial foi eficaz no recobrimento de recessões gengivais do tipo Classe I de Miller, mesmo em uma região de difícil execução da técnica.
The use of subepithelial connective tissue graft for root coverage on mandibular teeth
Keywords: Subepithelial connective tissue graft; Esthetics; Gingival recession; Enxerto conjuntivo subepitelial; Estética; Recessão gengival